MUHAMMAD SAW DAN PELETAKAN DASAR PERADABAN ISLAM - Ismail Suardi Wekke; R H Tamimi; Budy Sugandi (IAIN Manado, 2018)
Abstract. The history of pre and post of Islamic civilization in Arabia is certainly bipolar condition. In one side, pre-Islamic civilization occurred worst behaviors such as hostility, discord, injustice, and the suppression which deconstructed tradition in the Arab nation. Of course, it was different when Muhammad (Arabic descent) was born, there was a very significant changes from the scientific case, social, economic, and other aspects. Overall, all of aspects above has been reconstructed by the miracles of the Prophet, i.e. that is holy Qur'an as a basic guidelines and in the form of Prophet behaviors, sayings and way of life which accumulated in the Hadith was capable of shifting civilization that backward into a very advanced civilization in any lines. This research tries to construct and compare the Arab civilization, pre-prophets born to Prophets had been born and brought revolutionary mission with the emergence of a new civilization, the Islamic civilization. Keywords: Arabia pre-Islamic, the life of Muhammad, Islamic Civilization Abstrak. Sejarah pra-Islam dan pasca datangnya nabi Muhammad di tengah peradaban bangsa Arab tentunya merupakan suatu kondisi yang sangat bipolar. Di satu sisi, peradaban pra-Islam banyak terjadi perilaku buruk seperti permusuhan, perselisihan, ketidakadilan, penindasan bahkan pembunuhan merupakan suatu tradisi dekonstruktif dalam tatanan bangsa Arab. Tentunya, hal ini sangat berbeda ketika Muhammad saw. (keturunan Arab) lahir, terjadi perubahan tatanan yang sangat signifikan mulai dari konsteks keilmuan, sosial, ekonomi, dan aspek-aspek lainnya. Secara kompeherensif, aspek tersebut di atas direkonstruksi dari mukjizat nabi, yakni Alquran sebagai pedoman dasar dan berupa dari tata cara berperilaku nabi, ucapan dan way of life nabi yang terakumulasi dalam hadits mampu menggeser peradaban yang terbelakang menjadi perabadan yang sangat maju di berbagai lini. Penelitian ini mencoba untuk mengkonstelasikan dan mengkomparasikan peradaban bangsa Arab pra Nabi hingga Nabi dilahirkan dan membawa misi revolusioner dengan munculnya peradaban baru, peradaban Islam. Kata Kunci: Arab pra-Islam, kehidupan Muhammad, Peradaban Islam